On the relationship between milk yield and climatic factors - RAMACHANDRAN , V.S.; MURALI, N. M. (MAUSAM, 1992)
Statistical analysis was carried out between seasonal milk yield and some of the derived climatic variables at a semi-arid tropical locality in Bangalore. The study revealed that the milk yields varied from the highest (9, 3 lit/cow/day) in summer season to the lowest (8, 5 lit/cow/day) in winter season and almost the same in both the monsoon season (8, 7 and 8, 5 lit/cow/day during southwest and northeast monsoon seasons). It was envisaged that the climatic components like wind chill index had negative effect while wetness index and photo-thermal heat units had both positive (summer and winter seasons) and negative (two monsoon seasons) influences on seasonal milk yields.